2017
DOI: 10.1038/s41598-017-10711-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of gut Bifidobacterium population in healthy Japanese infants over the first three years of life: a quantitative assessment

Abstract: Bifidobacteria are important members of human gut microbiota; however, quantitative data on their early-life dynamics is limited. Here, using a sensitive reverse transcription-qPCR approach, we demonstrate the carriage of eight signature infant-associated Bifidobacterium species (B. longum, B. breve, B. bifidum, B. catenulatum group, B. infantis, B. adolescentis, B. angulatum and B. dentium) in 76 healthy full-term vaginally-born infants from first day to three years of life. About 21% babies carry bifidobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 61 publications
1
72
0
4
Order By: Relevance
“…We isolated a significant number of diverse bifidobacterial strains and species including members commonly associated with infants including B. infantis, B. longum, B. breve, and B. pseudocatenulatum from three healthy, breast-fed infants [48,49]. We identified genotypic and phenotypic differences between these strains and species within a single infant a Schematic illustrating experimental set-up and preparation of conditioned media for cross-feeding experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We isolated a significant number of diverse bifidobacterial strains and species including members commonly associated with infants including B. infantis, B. longum, B. breve, and B. pseudocatenulatum from three healthy, breast-fed infants [48,49]. We identified genotypic and phenotypic differences between these strains and species within a single infant a Schematic illustrating experimental set-up and preparation of conditioned media for cross-feeding experiments.…”
Section: Discussionmentioning
confidence: 99%
“…angulatum, and B. dentium), we reported that compared to infants born vaginally, cesarean-born infants have a noticeably lower carriage of major bifidobacterial groups during the first 3 months [21]. In addition, cesarean-born infants exhibit lower/delayed carriage of several bifidobacterial members, primarily B. catenulatum group, B. dentium, and B. infantis, during the first 6 months of life, and the number of Bifidobacterium species detected during the first 6 months also remains lower in cesarean-born infants [21]. However, again, these differences tend to disappear by 3 years of age.…”
Section: Early-life Gut Microbiota In Relation To the Mode Of Deliverymentioning
confidence: 94%
“…This suggests that the mother-baby transmission of bifidobacteria does occur to some extent even in cesarean-born babies, but the incidence and/or array of this transmission is relatively lower compared to that in the case of vaginal birth. Yet, these data hint that most of the bifidobacterial species in the newborn gut are acquired from the mother and that the birth mode could influence the evolution of these species during first few months of life [21].…”
Section: Early-life Gut Microbiota In Relation To the Mode Of Deliverymentioning
confidence: 99%
“…Nevertheless, some studies reported differences in microbiota between feeding types. Nagpal et al [30] followed the gut microbiome of healthy Japanese infants for 3 years according to their feeding types using highly sensitive reverse transcription quantitative PCR. Infants starting formula-fed supplementation as early as the first week of life were shown to have higher bifidobacterial carriage during first 6 months of life compared with exclusively breastfed counterparts.…”
Section: Discussion/conclusionmentioning
confidence: 99%